PROBLEM OF EMPIRICAL DISMUTATION IN TEACHING NATURAL SCIENCES - Witowski, Dariusz (European Scientific Journal, ESJ, 2014)
In 2006 on the fourth level of education new types of text tasks were introduced in Matura examination papers. Open tests relating to school experiment were supposed to increase the importance of experimenting in school labs. Test tasks such as: Suggest an experiment…, Note down the observations… should be considered easy because they have roots in empirical work of students and teachers during lessons. The analysis of passing rate of such test tasks on Matura examinations, compared with the results of research carried out on teachers who admit to do no or few lab experiments, reveals a problem existing in Polish schools. Further research proves the existence of a new problem of pedagogic, psychological and social nature that I noticed back in 2007. I called it empirical dismutation, which is a situation in which due to the lack of all elements necessary for it to arise, few people taking part in it achieve teaching success and the vast majority experience partial or complete degradation of success. The article enumerates the causes of pedagogic dismutation, suggests the methods of prevention and describes the threats arising if no prophylactic measures are taken.